Уходи красиво: [роман] / Т. В. Полякова - Полякова Татьяна Викторовна (Авантюрный детектив, 2011)
Экземпляры: аб. (2011) / Инвентарный номер: 47461 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 55 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6